Nudging for tax compliance - Armenak Antinyan; Zareh Asatryan (EconPol Forum, 2024)
Governments around the world increasingly use nudges to improve tax collection. Our meta-analysis evaluates the evidence gained from around 70 recent randomized trials. We find that simple reminders, tax morale, and deterrence nudges all increase tax compliance. The effectiveness of these interventions varies by nudge type and also depends on the context. We formulate policy recommendations as to who, when, and how to nudge.
Keywords: 330